KAJIAN HUKUM KRITIS ALIH FUNGSI LAHAN HUTAN BERORIENTASI KAPITALIS - Maladi, Yanis (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Agrarian inequalities that happening today, especially in relation to forest land conversion for oil palm cultivation, resulting high in forest space conflicts. The phenomenon of the extent of forest damage was caused by state policies that embrace the ideology of forest management based on government-based forest management rules which precipitates patterned repressive law. If the government keeps the forest as a source of state revenue in the name of development-oriented capitalist economy will be negatively impact so many people who become victims of development. To overcome the inequality of forest use, need to review the rules per-oriented laws exploitation (use-oriented) using a study critical legal study.Keywords : land conversion, capitalism, esoteric, critical legal studies